GC-MS Analysis and Activity Study of the Volatile Components of Huidouba. Issue 2 (4th March 2018) - Li, Lixia; Fu, Tingting; Wang, Qiang; Zou, Yuanfeng; Huang, Chao; Yin, Zhongqiong; Yang, Jiao; Liu, Yang; Feng, Dongmei; Feng, Xin
Abstract: The volatile oil extracted from the traditional Chinese medicine, Huidouba, was analyzed by gas chromatography-mass spectrometry (GC-MS) and the mass fractions of all these chemical components were tested by using peak area normalization method. 103 chemical compositions in total were identified, which accounted for 87.296% of the total amount of the volatile oil, mainly including hydrocarbons for 52.646%, alcohols for 15.483%, phenols for 6.205%, ketones for 1.211%, aldehydes for 4.718%, esters for 6.573% and nitrogenous substances for 0.46%.The analysis using AutoDock 4.2 showed that ferruginol was docked with the hemeoxygenase (1S8C), α-patchoulene was docked with the human sorbitol dehydrogenase (1PL7), vitamin A aldehyde was docked with the human retinal receptor (1EXX), phytol was docked with the natural anticoagulant (1LQV), and α-copaene was docked with the hexameric insulin (1TYL).Which play important roles in health, implicating the potential activity of these components in Huidouba volatile in diabetes treatment.